Reactivity Patterns Of Vanadium(iv/v)-oxo Complexes With Olefins In The Presence Of Peroxides: A Computational Study - Muhammad Qadri Effendy Mubarak; Sam P. de Visser (Royal Society of Chemistry (United Kingdom), 2024)
Dalton Trans., 2019,48, 16899-16910